IMPROVEMENT OF PROFESSIONAL TRAINING FUTURE TEACHERS BY MEANS FOREIGN LANGUAGE - Kadchenko, L.P. (Pedagogy of Higher and Secondary Education, 2001)
Effectiveness of foreign languages studying in professional training of future teachers is possible due to the realization of the following trends in work: forming professional, pedagogical, and linguistic interests of students by contents of educational information studied by them; teaching multiform methods and ways of cognitive activity; bringing the contents of educational information into accord with interests, motives, demands and professional aims of students.